2021
DOI: 10.1016/j.enpol.2021.112571
|View full text |Cite
|
Sign up to set email alerts
|

Energy poverty influences urban outdoor air pollution levels during COVID-19 lockdown in south-central Chile

Abstract: The effect of COVID-19 lockdowns on ambient air pollution levels in urban south-central Chile, where outdoor air pollution primarily originates indoors from wood burning for heating, may differ from trends in cities where transportation and industrial emission sources dominate. This quasi-experimental study compared hourly fine (PM 2.5 ) and coarse (PM 10 ) particulate matter measurements from six air monitors (three beta attenuation monitors; three low-cost sensor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 90 publications
(110 reference statements)
0
4
0
Order By: Relevance
“…The records correspond to measurements taken in the year 2022, which were filtered for the two months with the lowest average temperatures in the year (June-July, respectively), as demonstrated in other studies [37,38], as these months have a higher concentration of air pollutants. Additionally, to gain even more detailed insight into indoor air variables, the three days with the lowest temperatures of the season were selected (15-17 July 2022).…”
Section: Data Cleaning and Processingsupporting
confidence: 54%
“…The records correspond to measurements taken in the year 2022, which were filtered for the two months with the lowest average temperatures in the year (June-July, respectively), as demonstrated in other studies [37,38], as these months have a higher concentration of air pollutants. Additionally, to gain even more detailed insight into indoor air variables, the three days with the lowest temperatures of the season were selected (15-17 July 2022).…”
Section: Data Cleaning and Processingsupporting
confidence: 54%
“…In contrast, the change in SO 2 was ambiguous ( Hidalgo García and Arco Díaz, 2022 ; Tyagi et al, 2021 ), and even the opposite trend in O 3 was observed ( Cao et al, 2022 ). However, the air quality in some economically underdeveloped areas has not been improved because of the COVID-19 lockdowns ( Mandal et al, 2022 ; Martinez-Soto et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…We assume that in cities that have relatively lower mean PM and NO 2 annual means, such as Birmingham during this period (which are in attainment to EPA standard levels—see Table 1 ), such significant changes may not be observed [ 39 ]. Studies have demonstrated that the contributing factors to air quality changes during the COVID-19 lockdowns are complex and vary depending on urban/commercial vs. rural neighborhoods, primary energy sources used (wood vs. coal) and influence of secondary pollutants, such as Ozone in some regions [ 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%